TINJAUAN HUKUM TERHADAP PRODUK UMKM YANG BELUM MEMPUNYAI LABEL HALAL - Hapsari, Cinthia Mutiara (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Micro, small and medium enterprises (MSMEs) are one of the business sectors that can develop and be consistent in the economy of a country or region. This study aims to find out how legal protection efforts are. for micro, small and medium enterprises (MSMEs) who have not included the halal label from the perspective of the laws of the Republic of Indonesia and what are the legal sanctions for micro, small and medium enterprises (MSMEs) who have not included the halal label. This study uses a qualitative research method which is a study in the form of document studies or document study texts. This research is a study that focuses on the analysis of written materials based on their context. so researchers must try to find the theory. The results of this study indicate that supervision of the implementation of consumer protection is related to the inclusion of a halal label on MSME products and the application of statutory provisions